Dependability of the Explorer Autonomous Underwater Vehicle in Oil Plume Response Mission; Case Study of the Vehicle Roll Control - Azarsina, Farhood (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
Oil plume dispersion in water depth is an applied topic to study, and a practical way to respond to such a catastrophic event is to deploy an autonomous underwater vehicle (AUV) in the area. With notice that the underwater oil flows upward to the surface and in the meantime disperses into larger radii, a conical helix can be a suitable candidate for maneuvering about the oil spill.A helix maneuver requires steady control of the roll angle of the vehicle. Therefore, roll control adverse yaw, which originated in aviation, would be a concern for underwater navigation too. The correcting actuator signal that can adjust the vehicle's yaw angle, and therefore maintain its heading angle, shall be provided by the rudders or stern planes of the vehicle. Then the methodology of this research is to analyze the dependability of the rudder’s subsystem as a network of components in series. The dependability analysis that is performed here is in a series block diagram that is based on a minimal cut series. The results of this study show that the dependability of the engineering subsystems in an unmanned underwater vehicle can directly influence the outcome of a sensitive marine environmental protection project. Results show that the stern planes by more than a 90 percent chance can manage to control the maneuvering goals.